EKSPERIMEN SAINS ANAK USIA 5-6 TAHUN MELALUI PERMAINAN WATERBOOM MINI - Fajriati, Ruliana; Suyadi, Suyadi (UNIVERSITAS SLAMET RIYADI, 2020)
This research is motivated by the lack of variety of learning media in schools so that learning is less attractive to children and children cannot construct their own knowledge. The purpose of this study is to find out how science experiments through this mini Waterboom game in developing the scientific abilities of children aged 5-6 years. This research uses descriptive research with a qualitative approach. This research was conducted at Nasyithatun Nisa Kindergarten. The results of this study in addition to developing children's scientific abilities can also develop six aspects of the development of children, namely cognitive development, language, social-emotional, moral and religious, physical-motor and arts. In the ability of science there are three substances that are basically fulfilled by this game, namely science as a process, science as a product and science as a scientific attitude. ABSTRAKPenelitian ini dilatar belakangi dari kurangnya variasi media pembelajaran di sekolah sehingga pembelajaran kurang menarik bagi anak dan anak tidak bisa mengkonstruksi pengetahuannya sendiri. Tujuan dari penelitian ini yaitu untuk mengetahui bagaimana eksperimen sains melalui permainan waterboom mini ini dalam mengembangkan kemampuan sains anak usia 5-6 tahun. Penelitian ini menggunakan jenis penelitian deskriptif dengan pendekatan kualitatif. Penelitian ini dilaksanakan di TK Nasyithatun Nisa. Hasil penelitian ini selain mengembangkan kemampuan sains anak juga dapat mengembangkan enam aspek perkembaangan anak yaitu perkembangan kognitif, bahasa, sosial-emosional, moral dan agama, fisik-motorik serta seni. Dalam kemampuan sains ada tiga substansi secara mendasar yang dipenuhi permainan ini yaitu sains sebagai suatu proses, sains sebagai suatu produk dan sains sebagai suatu sikap keilmuan.